The neural substrate and underlying mechanisms of executive control fluctuations in primates - Mansouri, FA; Buckley, MJ; Tanaka, K (Elsevier, 2022)
Trial-by-trial alterations in response time have been linked to fluctuations of executive control and transient lapses of attention. Here, we report remarkable homologies in performance-dependent fluctuations of response time between humans and monkeys. We examined the effects of selective bilateral lesions in four frontal regions on control fluctuations in the context of a rule-shifting task. Lesions within orbitofrontal cortex (OFC), but not within superior-lateral prefrontal cortex, significantly exaggerated the performance-dependent fluctuations of control and prevented its restoration following feedback. Lesions within dorsolateral prefrontal cortex (DLPFC) or within anterior-cingulate cortex (ACC) led to instability of control and disruption of its link with monkeys’ upcoming decisions. Examining the activity of DLPFC and OFC cells shed more lights on the underlying neuronal mechanisms by showing that before the start of each trial, OFC cell activity conveyed detailed information regarding the current state of executive control and the likelihood of success or failure in the future decisions. This further emphasizes the crucial role of OFC in the trial-by-trial allocation (setting) of control to the ongoing task. These findings bring insights to the neural architecture of executive control in primates and suggest that DLPFC and ACC support sustained executive control, but OFC is more involved in setting and restoring the control.